Fatigue behavior enhancement of short fiber glass reinforced polyamide by adding phase change materials. (15th May 2016) - Casado, J.A.; Gutiérrez-Solana, F.; Carrascal, I.; Diego, S.; Polanco, J.A.; Hernández, D.
Abstract: High responsibility thermoplastic components subjected to dynamic forces show serious in-service thermal limitations. This paper shows that adding the adequate material with a phase-change, PCM, to a thermoplastic matrix component significantly increases its fatigue life. To do this, the fatigue resistance of short fibre-glass reinforced polyamide is analysed by means of monotonous fatigue tests on tensile specimens. Next, the design of the pieces of this material, used in high-speed rail fastenings, is optimised for fatigue efforts by means of accelerated single-piece tests. Finally, it is verified that the fatigue resistance of these pieces endowed with hydrated salt, Na2 S2 O3 ·5H2 O, which acts as a PCM, increases by a surprising 400% with respect to the reference pieces without PCM.